THE IMPACT OF INNOVATIVE TECHNOLOGIES ON PEDAGOGICAL ACTIVITY IN THE EDUCATIONAL PROCESS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article provides a scientific-theoretical and practical analysis of the impact of innovative technologies on pedagogical activity in the educational process. The study highlights the significance of innovative pedagogical technologies in improving teachers’ professional practice, enhancing educational effectiveness, and developing learners’ cognitive engagement and independent thinking skills. In addition, the role of digital technologies, interactive methods, and information and communication technologies within the modern education system is examined. The article substantiates that innovative approaches represent a key factor in the modernization of pedagogical activity.